THE ROLE OF LABORATORY IN THE EFFORTS OF INCREASING VOCATIONAL EDUCATION QUALITY IN INDUSTRIAL REVOLUTION 4.0 - Muhammad Hudan Rahmat; Marko Ayaki Lumbantobing (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2019)
The competition of working world in the industrial revolution era 4.0 requires many countries to improve themselves in producing the quality of human resources. Therefore, vocational education institutions as producers of workforce that ready to work have to produce the top notch output. This demand have to be immediately reflected and implemented in formal education and training programs. By the existence of laboratory, students are able to do anything to learn and practice their skills due to the characteristics of vocational education are more underlined in the development of learners' psychomotor aspects. Hence, the existence of laboratory has a crucial role for vocational education in order to enhance the quality of vocational education thus the improvement of vocational program quality for final graduates are achieved greatly.